2014
DOI: 10.1016/j.resp.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced interstitial pulmonary edema at sea-level in young and old healthy humans

Abstract: We asked whether aged adults are more susceptible to exercise-induced pulmonary edema relative to younger individuals. Lung diffusing capacity for carbon monoxide (DLCO), alveolar-capillary membrane conductance (Dm) and pulmonary-capillary blood volume (Vc) were measured before and after exhaustive discontinuous incremental exercise in 10 young (YNG; 27±3 yr) and 10 old (OLD; 69±5 yr) males. In YNG subjects, Dm increased (11±7%, P=0.031), Vc decreased (−10±9%, P=0.01) and DLCO was unchanged (30.5±4.1 vs. 29.7±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
(88 reference statements)
3
17
1
1
Order By: Relevance
“…The D M,CO values calculated via the multiple-FiO 2 method in the present study (Table 4) are similar to those previously reported (Ceridon et al., 2010; de Bisschop et al, 2012; Snyder et al, 2008; Taylor et al, 2014). However, the V C values found presently are similar to some (de Bisschop et al, 2012) but somewhat greater than other (Ceridon et al, 2010; Snyder et al, 2008; Taylor et al, 2014) previously reported data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The D M,CO values calculated via the multiple-FiO 2 method in the present study (Table 4) are similar to those previously reported (Ceridon et al., 2010; de Bisschop et al, 2012; Snyder et al, 2008; Taylor et al, 2014). However, the V C values found presently are similar to some (de Bisschop et al, 2012) but somewhat greater than other (Ceridon et al, 2010; Snyder et al, 2008; Taylor et al, 2014) previously reported data.…”
Section: Discussionsupporting
confidence: 92%
“…D M,CO values were significantly increased with exercise for all θ CO equations, while V C values were not significantly increased for any equation (Table 4). All equations yielded similar values to other studies for D M,CO and V C (Ceridon et al, 2010; de Bisschop et al., 2012; Snyder et al, 2008; Taylor et al, 2014). …”
Section: Resultssupporting
confidence: 81%
“…In healthy humans, exercise is associated with an increase in cardiac output and pulmonary perfusion pressure that causes both recruitment of under-perfused pulmonary capillaries and distension of already perfused pulmonary blood vessels, as evidenced by an increase in DLCO, Dm CO , and V C (La Gerche et al, 2010; Tamhane et al, 2001; Taylor et al, 2014). Therefore, it is crucial that measures of Dm CO and Vc increase accordingly in response to exercise, regardless of whether θ NO is assumed to be infinite or finite.…”
Section: Resultsmentioning
confidence: 99%
“…Individual contribution of each of these factors varies depending on the exposure. While clear evidence of cardiac and pulmonary abnormalities have not been found [82], individual variation in susceptibility [8,83] due either to variations in capillary strength, left ventricular relaxation, pulmonary vascular reactivity under conditions of exercise, and the instantaneous state of blood and fluid volume are likely to contribute to the development of pulmonary oedema.…”
Section: Discussionmentioning
confidence: 98%